Pengaruh Media Animasi Interaktif terhadap Kemampuan Visualisasi Matematis Siswa - Siti Nurseha (REGRESI: Journal of Mathematics Education and Application, 2025)
This study aims to analyze the effect of using interactive animation media on students’ mathematical visualization ability. Mathematical visualization ability is one of the essential competencies in mathematics learning, as it plays a significant role in helping students understand abstract concepts through visual representations, images, and dynamic models. However, in conventional teaching practices, students often experience difficulties in constructing mental representations of mathematical objects. This research employed a quantitative approach with a quasi-experimental design using a pretest–posttest control group design. The subjects of the study were students from a secondary school who were divided into an experimental class and a control class. The research instrument consisted of a mathematical visualization ability test that had been validated and tested for reliability. The data were analyzed using inferential statistical tests to determine differences in improvement between the two groups. The results indicate that the use of interactive animation media has a significant effect on improving students’ mathematical visualization ability. Students who learned through interactive animation media showed greater improvement compared to those who learned using conventional methods. These findings suggest that interactive animation media are effective in helping students develop visual and spatial understanding of mathematical concepts and can therefore be recommended as an innovative alternative instructional medium in schools